Assessment of undergraduates’ real-world outcomes of critical thinking in everyday situations - Franco, Amanda Helena Rodrigues (2017)
Critical thinking is a kind of ‘‘good’’ thinking that integrates a set of cognitive skills and dispositions to use those skills with knowledge to increase the chances of success in academic settings, job market, and daily life. The impact of critical thinking on life events, in face of everyday decisions and challenges, is still unclear, and further research is needed. In this exploratory study, a sample of 230 first-year students of a Bachelor’s Degree or a Master’s Degree in Portugal completed an experimental Portuguese version of the Real-World Outcomes, a self-report inventory measuring everyday negative life events that are mediated by a lack of critical thinking. Based on exploratory factor analysis results and theoretical premises, changes were made to the Portuguese version of the inventory that was administered, and items were aggregated into six dimensions, creating a new version that is more familiar to Portuguese young adults in college. This original proposal of the inventory presents six types of negative life events resulting from a lack of critical thinking: health neglect, mismanagement, slackness, poor impulse control, academic negligence, and rashness. Both limitations and future potentialities of this version are presented.